2021
DOI: 10.3390/dairy2020017
|View full text |Cite
|
Sign up to set email alerts
|

A2 Bovine Milk and Caprine Milk as a Means of Remedy for Milk Protein Allergy

Abstract: A new type of cow’s milk, called A2 milk, has appeared in the dairy aisles of supermarkets in recent years. Cows’ milk generally contains two major types of beta-casein as A1 and A2 types, although there are 13 genetic variants of β-casein: A1, A2, A3, A4, B, C, D, E, F, H1, H2, I and G. Studies have shown that A1 β-casein may be harmful, and A2 β-casein is a safer choice for human health especially in infant nutrition and health. The A2 cow milk is reportedly easier to digest and better absorb than A1 or othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 41 publications
1
19
0
2
Order By: Relevance
“…Humans consume milk from ruminant species as whole milk, dairy products, or dairy ingredients. Ruminant milk from different species has been extensively studied, selected and modified (Pietrzak-Fie cko and Kamelska-Sadowska 2020; Haug, Høstmark, and Harstad 2007) to address human nutritional and health requirements (Gorlov et al 2019;Park and Haenlein 2021;Suri et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Humans consume milk from ruminant species as whole milk, dairy products, or dairy ingredients. Ruminant milk from different species has been extensively studied, selected and modified (Pietrzak-Fie cko and Kamelska-Sadowska 2020; Haug, Høstmark, and Harstad 2007) to address human nutritional and health requirements (Gorlov et al 2019;Park and Haenlein 2021;Suri et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This could be as a result of the selection method which favours one genetic variant in these countries over the years. Indeed, in the past three decades, casein have drawn a special interest and attention to scientists and dairy consumers due to the potential relationship between beta-casein genotype of the bovine milk protein and the health of cow milk consumers (Daniloski et al, 2021;Joshi et al, 2021;Park & Haenlein, 2021). Therefore, it has been reported that the beta-casomorphin-7 (BCM-7) generated from A1 variant bovine milk causes human health hazards.…”
Section: Discussionmentioning
confidence: 99%
“…A fração A1 da β-caseína quando passa pela digestão gastrointestinal libera um peptídeo chamado β-casomorfina-7 (BCM-7) que parece ser o fator primário para o desenvolvimento de problemas digestivos relacionados ao consumo de leite bovino (Park & Haenlein, 2021).…”
Section: Composição Do Leite Caprinounclassified